Development Module Of Information Services For Students' Maturity In Career Decision Making - Feby Najmah Khairiyah; Dina Sukma (Jurnal Penelitian Pendidikan IPA, 2024)
Adolescence is an important period in the development of high school students, where they begin to find their identity and determine their career direction. This process is often accompanied by challenges, such as the lack of accurate and transparent information regarding career choices. This study aims to develop a module service that is valid in content and design, practical, and effective to assist students in making career decision information. This research uses the research and development (R&D) method. The research design model used in this study is the ADDIE (Analysis-Design-Develop-Implement-Evaluate) research and development model. The respondents in this study were 3 expert lecturers for content validation, 2 expert lecturers for display validation, 3 guidance and counseling teachers for practicality testing, and 30 students for effectiveness testing. The results of the study indicate that the developed service module is valid in terms of content and design, and is also practical and effective for the maturity of students' career decision-making information